2021
DOI: 10.1371/journal.pone.0244973
|View full text |Cite
|
Sign up to set email alerts
|

Floral hosts of leaf-cutter bees (Megachilidae) in a biodiversity hotspot revealed by pollen DNA metabarcoding of historic specimens

Abstract: South Africa is a megadiverse country with three globally recognised biodiversity hotspots within its borders. Bees in particular show high diversity and endemism in the western part of the country. Not much is currently known about the floral host preferences of indigenous bees in South Africa, with data only available from observational studies. Pollen metabarcoding provides provenance information by utilising DNA analyses instead of floral visitation and traditional microscopic identification to identify po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…This is particularly the case where baseline data exists and has been collected through traditional methods. However, there are cases where samples have been captured and preserved: e.g., museum specimens of pollinators (Gous et al, 2021;Simanonok et al, 2021), slides of pollen collections (Marcel Polling et al, 2022), and these have been analysed through DNA metabarcoding, providing scope to analyse contemporary and historical samples, and assess changes from baseline ecological conditions. As more long-term studies are completed using DNA metabarcoding, these methods could be used to understand recent change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly the case where baseline data exists and has been collected through traditional methods. However, there are cases where samples have been captured and preserved: e.g., museum specimens of pollinators (Gous et al, 2021;Simanonok et al, 2021), slides of pollen collections (Marcel Polling et al, 2022), and these have been analysed through DNA metabarcoding, providing scope to analyse contemporary and historical samples, and assess changes from baseline ecological conditions. As more long-term studies are completed using DNA metabarcoding, these methods could be used to understand recent change.…”
Section: Discussionmentioning
confidence: 99%
“…Historical specimens can also be used not only for temporal analysis of forage use but can help increase sample size for spatial analysis. For example, Gous, Eardley, Johnson, Swanevelder, and Willows-Munro (2021) sampled pollen from museum specimens of multiple species from varying regions in South Africa across large temporal scale to assess the relationship between resource use and geographic range of species. There is similar potential to use herbarium specimens to look at past distributions and morphology of plants to check for plant-pollinator mismatches.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Both studies found that the amount and diversity of pollen collected was strongly influenced by season, most likely influenced by the phenology of surrounding plants [80,81]. In addition to tracking contemporary foraging habits, DNA metabarcoding has been shown to be a useful tool for analysing pollen from historical specimens [78,82,83]. By sequencing pollen obtained from museum specimens, Simanonok et al [83] successfully identified the plants used by an endangered bumblebee species over 100 years, vastly improving current knowledge of resource use and mechanisms of decline.…”
Section: How Does Foraging Change Throughout Time and Space?mentioning
confidence: 99%
“…As an alternative to morphological pollen identification, DNA metabarcoding has been shown to provide increased taxonomic resolution and it has been used successfully on bee-collected pollen ( Bänsch et al, 2020 ; Elliott et al, 2021 ; Gous et al, 2021 ; Richardson et al, 2019 ) as well as airborne pollen ( Banchi et al, 2020 ; Brennan et al, 2019 ; Campbell et al, 2020 ; Kraaijeveld et al, 2015 ; Uetake et al, 2021 ). For grasses (Poaceae) for example, a recent study has shown that pollen of a small subset of all species present in the UK is likely to have a disproportionate influence on human health ( Rowney et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%